The Reliability of Transabdominal Cervical Length Measurement Compared with Transvaginal Measurement at 16-24 Weeks of Gestation - Nattaya Buathum (Thai Journal of Obstetrics and Gynaecology, 2019)
Objectives: To determine reliability of transabdominal cervical length (TACL) compared with transvaginal cervical length (TVCL) at 16-24 weeks of gestation. Materials and Methods: A prospective study was conducted in the Obstetrics and Gynecology Department at Phramongkutklao Hospital between 27 March 2017 and 29 December 2017. Singleton pregnant women who underwent ultrasound between 16-24 weeks of gestation with any indication were enrolled. Women with a history of cervical surgery, uterine contractions and vaginal bleeding were excluded. After voiding, TACL was measured followed by TVCL as per the protocols stipulated by the Fetal Medicine Foundation (2014). Demographic and medical data were collected. Cervical length measurements from both methods were compared, and the factors accounting for differences in measured lengths were considered. Results: One hundred and forty-two women with singleton pregnancies agreed to participate in the study. Satisfactory TACL images could not be obtained within 5 min in 12 (8.6%) of the 142 women, and were excluded from the analysis. Of a total of 130 singleton pregnant women, mean TACL and TVCL values were found to be 39.3 ± 6.4 mm and 41.5 ± 7.4 mm, respectively. The mean TACL was found to be shorter than the mean TVCL by an average of 2.2 mm (p < 0.001). An intraclass correlation coefficient between both procedures was found to be 0.443 which was statistically significant (p < 0.001). Similarly, the difference between TVCL and TACL measurements decreased as BMI increased with statistical significance (p = 0.043). The 5th percentile of TACL and TVCL was 31 mm and 32 mm, respectively. None of the patients had a TACL and TVCL < 25 mm which is defined as a short cervix. Conclusion: The TACL assessment was possible to carry out 91.4% of pregnant women and was moderately correlated with TVCL, therefore, it may be considered as an initial screening tool for cervical length assessment in pregnant women at low-risk for preterm delivery.